Facet-selective interface design of a BiOI(110)/Br-Bi2O2CO3(110) p–n heterojunction photocatalyst. Issue 45 (6th November 2017) - Peng, Yin; Liu, Ting; Xu, Jian; Wang, Ke Ke; Mao, Yan Ge
Abstract : A BiOI(110) /Br-BOC(110) p–n heterostructure photocatalyst with a high interface quality was designed and synthesized by facet-dependent selective adsorption. Abstract : The facet-selective interface design for photocatalytic materials has been proven to be a versatile approach to enhance their photocatalytic performance. In this article, BiOI(110) /Br-Bi2 O2 CO3(110) p–n heterostructures were designed and synthesized by facet-dependent selective adsorption. Ultra-thin BiOI nanosheets uniformly grow on the (110) facet of a Br-Bi2 O2 CO3 nanoplate by crystallographically oriented epitaxial growth, which results in the high interface quality. The (110) facet that forms the interface is also the electron-active surface of Br-Bi2 O2 CO3, which improves the migration rate of the photoelectrons across the interface to the surface reactive sites. The photocatalytic activity of the as-made products is evaluated by the degradation of methyl orange (MO) under visible light irradiation. The results show that the BiOI(110) /Br-Bi2 O2 CO3(110) p–n heterostructure displays higher photocatalytic activity than pure phase Br-Bi2 O2 CO3 and BiOI, and 100% of the MO can be degraded in 30 min under visible light irradiation. This enhanced photocatalytic performance is attributed to the synergistic effect of the high interface quality, high migration rate of the separated electrons to the surface active sites and suitable band alignment of the BiOI and Br-Bi2 O2 CO3 . This work offers an effective route to design the junction structures with a facet-selective interface.